2002
DOI: 10.1271/bbb.66.378
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Transport of the Bioactive Tripeptide, Val-Pro-Pro, in Human Intestinal Caco-2 Cell Monolayers

Abstract: Some of the food-derived tripeptides with angiotensin converting enzyme (ACE)-inhibitory activity have been reported to be hypotensive after being orally administered. The mechanism for the intestinal transport of these tripeptides was studied by using monolayer-cultured human intestinal Caco-2 cells which express many enterocyte-like functions including the peptide transporter (PepT1)-mediated transport system. Val-Pro-Pro, an ACE-inhibitory peptide from fermented milk, was used as a model tripeptide. A signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
167
2
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(187 citation statements)
references
References 30 publications
10
167
2
6
Order By: Relevance
“…For instance, the tripeptide exerts chemotactic effects on fibroblasts, peripheral blood neutrophils and monocytes in cell culture systems [13][14][15] . Based on the size, the tripeptides are expected to be suitable for trans-epithelial transport 16 . Aito-Inoue et al 17 investigated the transport of Gly-Pro-Hyp across the intestinal brush-border membrane (BBM) in a porcine BBM model.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the tripeptide exerts chemotactic effects on fibroblasts, peripheral blood neutrophils and monocytes in cell culture systems [13][14][15] . Based on the size, the tripeptides are expected to be suitable for trans-epithelial transport 16 . Aito-Inoue et al 17 investigated the transport of Gly-Pro-Hyp across the intestinal brush-border membrane (BBM) in a porcine BBM model.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 It has been suggested that the mechanism of the antihypertensive effect exerted by such tripeptides is ACE inhibition. 6,7 Sipola et al 7 reported that the BP at the end of a trial in rats that had consumed peptide-enriched fermented milk was 21 mmHg lower than the BP of rats that had consumed water, and 10 mmHg lower than the BP of rats that had consumed Calpis s .…”
Section: Discussionmentioning
confidence: 99%
“…27) We examined IEC permeability to the antihypertensive tripeptide VPP, derived from bovine -casein, using Caco-2 monolayers cultured on semipermeable membranes. 28) The results suggested that VPP is transported across human IEC monolayers via the paracellular route rather than by the PepT1-mediated transport pathway (Fig. 3).…”
Section: Transport Pathways For Oligopeptidesmentioning
confidence: 93%